ICTHYOFAUNAL DIVERSITY OF BHARATHAPUZHA RIVER AT PALAKKAD DISTRICT, KERALA. - DIVYA.K.R; K.MANONMANI (International Journal of Pharma and Bio Sciences, 2014)
Aquatic populations interact with the physico-chemical and biological factors in their habitat. Any change in the habitat can induce stress on the life forms. The major water bodies and rivers in Kerala are not free from the pollution stress of varying degrees due to the influx of effluents from nearby factories, pesticides and fertilizers from cultivating areas, besides urban and rural sewages.The survey yielded 23 species of fresh water fishes belonging to 10 families and 5 different orders. Oreochromis mossambica and Oncorhychus mykiss were recorded as introduced species. Cyprindae members were the dominant forms in all sampling stations. Fishes were more abundant during monsoon season.